Gremlins - Dante, Joe.; Moore, Arnie; Don Steele; John Louie; Keye Luke; Scott Brady; Susan Burgess; Hoyt Axton (USA Amblin Entertainment, 1984)
Minature green monsters tear through the small town of Kingston Falls. Hijinks ensue as a mild-mannered bank teller releases these hideous loonies after gaining a new pet and violating two of three simple rules: No water (violated), no food after midnight (violated), and no bright light. Hilarious mayhem and destruction in a town straight out of Norman Rockwell. So, when your washing machine blows up or your TV goes on the fritz, before you call the repair man, turn on all the lights and look under all the beds. 'Cause you never can tell, there just might be a gremlin in your house.
A boy inadvertantly breaks 3 important rules concerning his new pet and unleashes a horde of malevolently mischievous monsters on a small town.
Chris Columbus
Languages : English
Subtitles : Turkish, English, Spanish
Keywords: Fantasy; Horror; Comedy